Antarctic-like temperature variations in the Tropical Andes recorded by glaciers and lakes during the last deglaciation. (1st November 2020) - Martin, L.C.P.; Blard, P.-H.; Lavé, J.; Jomelli, V.; Charreau, J.; Condom, T.; Lupker, M.; ,; Arnold, M.; Aumaître, G.; Bourlès, D.L.; Keddadouche, K.
Abstract: The respective impacts of Northern and Southern Hemispheric climatic changes on the Tropics during the last deglaciation remain poorly understood. In the High Tropical Andes, the Antarctic Cold Reversal (ACR, 14.3–12.9 ka BP) is better represented among morainic records than the Younger Dryas (12.9–11.7 ka BP). However, in the Altiplano basin (Bolivia), two cold periods of the Northern Hemisphere (Heinrich Stadial 1a, 16.5–14.5 ka BP, and the Younger Dryas) are synchronous with (i) major advances or standstills of paleoglaciers and (ii) the highstands of giant paleolakes Tauca and Coipasa. Here, we present new cosmic ray exposure (CRE) ages from glacial landforms of the Bolivian Andes that formed during the last deglaciation (Termination 1). We reconstruct the equilibrium line altitudes (ELA) associated with each moraine and use them in an inverse algorithm combining paleoglaciers and paleolake budgets to derive temperature and precipitation during the last deglaciation. Our temperature reconstruction (ΔT relative to present day) yields a consistent regional trend of progressive warming from ΔT = −5 to −2.5 °C during 17–14.5 ka BP, followed by a return to colder conditions around −4 °C during the ACR (14.5–12.9 ka BP). The Coipasa highstand (12.9–11.8 ka BP) is coeval with another warming trend followed by ΔT stabilization at the onset of the Holocene (ca. 10 ka BP), around −3 °C. Our results suggest that, during the last deglaciation (20–10 ka BP) atmospheric temperatures in the Tropical Andes mimicked Antarctic variability, whereas precipitation over the Altiplano was driven by changes in the Northern Hemisphere. Highlights: Cosmic ray exposure ages and paleo-ELAs determined for Bolivian Andes late-glacial moraines. New 14C shoreline ages constrain the depth of paleolake Coipasa (∼12.5 cal kyr BP). Temperature and precipitation reconstructed from coupled glacier-lake modeling. Lake-induced precipitation recycling effect accounted in reconstruction. Precipitation modulated by Northern Hemisphere, temperatures by Antarctic during 19–11 ka BP.